Groups Whose Nonlinear Irreducible p-Brauer Characters are Real Valued. Issue 1 (2nd January 2016) - Li, Yali; Zeng, Jiwen; Chen, Xiaoyou
Abstract : Let p be a given prime. A finite group G whose all nonlinear irreducible p -Brauer characters are real valued is called a p -regular ℝ1 -group. The aim of this article is to show some results about the structures of p -regular ℝ1 -groups. In particular, we will build the connections between p -regular ℝ1 -groups and p -modular Frobenius groups. If these results apply to a finite group G with p ∤| G |, we obtain similar results about finite groups whose nonlinear irreducible characters are real valued, and establish connections between these groups and Frobenius groups.